Gastric protein digestion of cow, goat, and sheep milk is not reflected in the amino acid appearance in the blood of suckling piglets - Roy D; Montoya CA; Stroebinger N; Hodgkinson SM; Ye A; McNabb WC; Moughan PJ; Singh H (Elsevier Inc on behalf of the American Dairy Science Association, 2025)
Structural changes in milk during gastric digestion are a key driving factor for the rate of digestion of nutrients in the gastrointestinal tract. Thus, the influence of gastric coagulation behavior on the kinetics of protein digestion of raw cow, goat, and sheep whole milk in the stomach was investigated using the 3-wk-old suckled male piglet as an animal model for human infants. Piglets received a single meal of fresh raw milk normalized for protein content, and were slaughtered at 0, 30, 90, 150, or 210 min postprandially. Gastric chyme and cardiac blood samples were collected. Gastric pepsin activity, rate of protein hydrolysis, and gastric emptying of AA were determined along with how these changes influence the appearance of AA in the plasma. The disappearance rates of individual proteins (especially β-LG and αS-CN), total digested proteins entering the small intestine, as well as the gastric emptying of some AA (proline, leucine) were (or tended to be) greater for goat and sheep milk than for cow milk. Differences in plasma concentrations for some AA (e.g., leucine) were observed across milk types, but they did not directly reflect changes in gastric protein digestion and the gastric emptying of AA. In conclusion, a combination of protein (and AA) composition, susceptibility of specific proteins to hydrolysis, and the nature of the curd structure formed influenced the digestion behavior of milk proteins in the stomach and their subsequent release into the small intestine.
Keywords: milk of different species; gastric protein digestion; gastric emptying of amino acids; appearance of blood amino acids; piglet model